How to make compost with Gliricidia sepium leaves and apply it in your fields - Gosling, Amanda; Center for International Forestry Research and World Agroforestry (2024)
This poster provides the key steps for making compost with Gliricidia sepium leaves and how to apply it in the field. It lists the materials needed and provides handy tips and common mistakes to avoid. The poster forms part of the Climate-Smart Forage and Feed Innovations training package that was co-developed with the Center for International Forestry Research and World Agroforestry (CIFOR-ICRAF) Tanzania and Malawi teams to accelerate the spillover process of validated AICCRA technologies. The poster content is based on knowledge materials sourced from the AICCRA Zambia team and their respective project partners (Community Markets for Conservation (COMACO) and Mediae.